2005
DOI: 10.1111/j.1600-0897.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG, IgA and IgM Antibodies against FSH: Serological Markers of Pathogenic Autoimmunity or of Normal Immunoregulation?

Abstract: We showed that anti-FSH-antibodies were present in controls and their production decreased during pregnancy. Endometriosis and PCOS were associated with higher values of anti-FSH-immunoglobulin (Ig)A, anti-V14D-IgA, and endometriosis with anti-V14D-IgG. Our data suggest that anti-FSH-IgA could be a marker of ovarian disorders that cause infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…In the field of obstetrics and gynecology, preeclampsia, recurrent miscarriage, endometriosis (25), fibroids (26), several malignant tumors (27), and ovarian diseases such as premature ovarian failure (POF) have been shown to be associated with autoimmunologic processes. Regarding PCOS, studies on autoimmunity yielded conflicting results (17)(18)(19)(20)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the field of obstetrics and gynecology, preeclampsia, recurrent miscarriage, endometriosis (25), fibroids (26), several malignant tumors (27), and ovarian diseases such as premature ovarian failure (POF) have been shown to be associated with autoimmunologic processes. Regarding PCOS, studies on autoimmunity yielded conflicting results (17)(18)(19)(20)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 98%
“…The heterogenous data in PCOS might be related to methodological differences and by the multiplicity of potential immune targets used. These targets comprise various steroidogenic enzymes, gonadotropins and their receptors, the corpus luteum (CL), zona pellucida (ZP), and oocyte (17)(18)(19)(20)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the presence of anti‐FSH antibodies (IgG, IgM and IgA) on healthy non‐pregnant women and a decrease in IgG and IgM on uncomplicated pregnancy 15 and an increase in those antibodies on infertile women 15, 16. The levels of anti‐FSH IgM antibodies were associated with peripheral FSH levels on patients with tubal and male factor infertility 17.…”
Section: Discussionmentioning
confidence: 99%
“…Although many hypotheses concerning the pathogenesis of PCOS have been proposed, none fully explain the heterogeneous characteristics of the syndrome [24][25][26].…”
Section: Discussionmentioning
confidence: 99%